2019
DOI: 10.24953/turkjped.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and laboratory findings in children hospitalized with acute Epstein-Barr virus infection: a crosssectional study in a tertiary care hospital

Abstract: Devrim İ. Clinical features and laboratory findings in children hospitalized with acute Epstein-Barr virus infection: a cross-sectional study in a tertiary care hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…The incidence of overall rash among IM children treated with antibiotics in this study was 13.04%, which was lower than that recorded in most studies ( 4 6 , 8 , 9 , 12 ) but close to that reported by Davis (14.89%) ( 7 ), Hocqueloux et al (15.32%) ( 10 ), and Misirlioglu et al (16.67%) ( 11 ). Furthermore, only 46.70% of rashes in this study overall were probably associated with antibiotic exposure, so the actual incidence (7.79%) of antibiotic-induced rash was much lower.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The incidence of overall rash among IM children treated with antibiotics in this study was 13.04%, which was lower than that recorded in most studies ( 4 6 , 8 , 9 , 12 ) but close to that reported by Davis (14.89%) ( 7 ), Hocqueloux et al (15.32%) ( 10 ), and Misirlioglu et al (16.67%) ( 11 ). Furthermore, only 46.70% of rashes in this study overall were probably associated with antibiotic exposure, so the actual incidence (7.79%) of antibiotic-induced rash was much lower.…”
Section: Discussionsupporting
confidence: 60%
“…Since fever, pharyngitis, fatigue, and lymphadenopathy are common presenting symptoms in the outpatient setting, IM is often mistaken for other entities, such as acute bacterial tonsillitis ( 3 ). However, despite the fact that IM is a benign self-limiting disease that does not require antimicrobial therapy, previous studies have demonstrated that 54.30% to 84.00% of IM patients continue taking antibiotics empirically throughout the course of their disease ( 4 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 Regarding laboratory parameters, the most frequent abnormality was elevated liver enzymes (54%), as previously described in other studies. 12 Interestingly, the increase in transaminases was particularly frequent in febrile patients (69%) and in the EBV-CMV group (62%).…”
Section: Discussionmentioning
confidence: 95%
“…IM can often present atypically [41], particularly in younger patients (<5 years age group) with many cases going undiagnosed - particularly if the diagnosis relies solely on the detection of nonspecific heterophile antibodies (HAs) to confirm clinically suspect cases [42,43]. Detection of HAs, most often performed using the Monospot test, is a specific yet insensitive test for diagnosing IM, particularly in the <5-year age group [44,45,46 ▪ ,47]. Patients who present with atypical lymphocytes (mononucleosis) on microscopy and have a low HA titre result should always have follow up specific EBV serology performed when the suspicion of IM is high [23].…”
Section: Epidemiologymentioning
confidence: 99%